2012
DOI: 10.1021/jp303645p
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-Doped TiO2 and Carbon, Tungsten-Codoped TiO2 through Sol–Gel Processes in the Presence of Melamine Borate: Reflections through Photocatalysis

Abstract: A series of C-doped, W-doped, and C,W-codoped TiO2 samples have been prepared using modified sol–gel techniques. Reproducible inexpensive C-doping arises from the presence of melamine borate in a sol–gel mixture, whereas W-doping is from the addition of tungstic acid to the sol. The materials have been characterized using elemental analysis, N2 physisorption (BET), thermogravimetric analysis, X-ray diffraction, Raman, X-ray photoelectron, UV–vis spectroscopies, and photocatalytic activity measurements. Doping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(83 citation statements)
references
References 74 publications
5
73
1
2
Order By: Relevance
“…The difference in the fitting peak for Ti2p of 454.5 eV and 458.3 eV is potentially resulted from the presence of CeTieO bond in the TiO 2 lattice that the electronegativity of C (2.55) is lower than that of O (3.44) which results in more electron-rich in TieO bond and further affects the difference in binding energy. This may also indicate the lattice distortion due to the presence of C atom (Neville et al, 2012), as similarly observed in the XPS spectra of other Ti-Bran catalysts. Ti content (Table 1) was also quantified via ICP/MS and was found to be in the range of 8e40 wt% of the final materials in the Ti-Bran samples after partial removal of the organics from wheat bran.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…The difference in the fitting peak for Ti2p of 454.5 eV and 458.3 eV is potentially resulted from the presence of CeTieO bond in the TiO 2 lattice that the electronegativity of C (2.55) is lower than that of O (3.44) which results in more electron-rich in TieO bond and further affects the difference in binding energy. This may also indicate the lattice distortion due to the presence of C atom (Neville et al, 2012), as similarly observed in the XPS spectra of other Ti-Bran catalysts. Ti content (Table 1) was also quantified via ICP/MS and was found to be in the range of 8e40 wt% of the final materials in the Ti-Bran samples after partial removal of the organics from wheat bran.…”
Section: Resultssupporting
confidence: 57%
“…Co-doping of C and N Yang et al, 2008), metal and non-metal co-doping (Neville et al, 2012;Shen et al, 2008; were reported to render materials with high visible light response.…”
Section: Introductionmentioning
confidence: 99%
“…30 To our best knowledge, there is no direct experimental demonstration on the effect of codoping TiO 2 for PEC application because of the lack of suitable doping methods for donor (metallic) dopants. Previous methods of doping TiO 2 with metallic donors typically introduced the dopants during the synthesis stage of TiO 2 with methods, such as sol-gel 23,26,31 , hydrothermal 32 , sputtering 27 and solution combustion 33 . All these in-situ doping methods change the crystallinity/morphology compared with undoped TiO 2 , preventing the isolation of the doping effect from crystallinity/morphology effects on the PEC performance.…”
mentioning
confidence: 99%
“…(W + C) codoped TiO 2 synthesized by Neville et al [109] and by Xiao et al [110], and (N + V) co-doped TiO 2 synthesized by Xu et al [111], also exhibited similar red-shifts of the absorption edge. Improving the catalytic activity by (W + C) co-doping is inconclusive, and Xiao et al demonstrated an increased photocatalytic activity with (W + C) co-doping compared to the undoped case [110], while the opposite was observed by Neville et al [109]. The presence of elemental C and Ti-O-C bonding [102,108] suggests that doped C mostly remains in its elemental phase, with only a relatively minor amount incorporated into TiO 2 in the form of interstitial or anion substitutional defects.…”
Section: Band-gap Engineering Of Tiomentioning
confidence: 66%
“…The deviation was attributed to the low concentration of dopant and N 2 adsorption on the surface [102]. (W + C) codoped TiO 2 synthesized by Neville et al [109] and by Xiao et al [110], and (N + V) co-doped TiO 2 synthesized by Xu et al [111], also exhibited similar red-shifts of the absorption edge. Improving the catalytic activity by (W + C) co-doping is inconclusive, and Xiao et al demonstrated an increased photocatalytic activity with (W + C) co-doping compared to the undoped case [110], while the opposite was observed by Neville et al [109].…”
Section: Band-gap Engineering Of Tiomentioning
confidence: 91%